Virtualized Simulation for Military Concept Development and Experimentation : The Cerebro Battle Lab, a Case Study - Knobbout, J.J.; oude Egbrink, D.F.; Lubsen, Z.A. (I/ITSEC, 2023)
In recent years, virtualization technologies have become standard practice in many industries, mainly due to their ability to provide a flexible computing environment at a fraction of the cost and time required for traditional approaches. This paper presents a case study of a unique application of virtualization in the military domain, specifically in the area of concept development and experimentation (CD&E). The Netherlands Aerospace Centre has invested in the development of a virtualized facility, called the Cerebro Battlelab, to support research into new military concepts and the simulation of large-scale scenarios for the Netherlands Armed Forces. The authors describe the design and implementation of the battlelab that hosts various types of simulation software, including flight simulators, on virtual machines in a secure vSphere server infrastructure. This allows operators and researchers to run simulations and experiments in a controlled and repeatable manner, while providing greater flexibility and scalability compared to alternative methods, like standard desktops or keyboard-video-mouse (KVM) setups. This paper also describes the trade-off analysis that led to the decision to use a virtual desktop infrastructure (VDI), as well as the technical aspects of implementing a VDI with low-latency and graphics-intensive requirements, and the operational benefits and challenges encountered during use. This case study provides valuable insights for anyone who is interested in the virtualization of simulation systems in the military and defense industry, especially those looking to implement similar solutions in their own organizations.